Study of Economic Structure and Leading Sectors in South Bengkulu Regency - Teresha Amanda (Universitas Muhammadiyah Palembang, 2023)
This research was conducted with the aim of knowing the economic structure of South Bengkulu Regency and what sectors will be the leading sectors so that the sector produces benefits for the development of the economic sector in the region. The research was conducted in South Bengkulu Regency. South Bengkulu has a GRDP that is relatively larger than other districts. This is an indication that this district has an economic advantage when compared to other districts. The data used in this study are secondary data from 2017 – 2021. The basic data used are data on GDP and economic growth This study uses LQ, DLQ, Shiftshare, and combination (overlay) analysis. The results of research in agriculture, forestry, and fisheries (A) have the highest value ranging from 32.54% to 34.30% in the economic structure of GDP on the basis of constant prices and prevailing prices. The field of Electricity and Gas Procurement (D) produces the smallest benefit to GDP, which ranges from 0.08% - 0.10%. The results of LQ, DLQ, and Shiftshare analysis show that there are 7 sectors in South Bengkulu Regency that have positive values. This means that the sector has a high GDP value and has the potential to become a leading sector in the future.